Política pública de acesso aberto à produção científica: o caso do Repositório Institucional da Universidade Federal de Lavras - Medeiros, Simone Assis (2013)
This thesis was carried out in order to understand the formulation process of the Institutional Information (PII), more specifically the UFLA Institutional Repository (RIUFLA) and recommend adjustment of actions for the implementation of this policy. Among the themes that permeate the field of public policies in Brazil, it is currently a State concern the provision of information activities in science, technology and research, through its federal institutions of higher education. Currently, the Brazilian Institute of Information in Science and Technology IBICT, in partnership with the Financier of Studies and Projects (FINEP), has been supporting universities and research institutions in the implementation of institutional repositories (IR), in order to promote access to and dissemination of scientific production. To promote open access scientific information with the deployment of repositories, IBICT also recommends that institutions, when setting up their repositories, implement a PII that turns mandatory the deposit of scientific production by researchers from institutions. Thus, we highlight the initiatives of formulation and implementation of institutional policies information in the context of higher education institutions in Brazil and the importance of implementing IRs as a tool to facilitate and ensure open access and visibility to scientific production. Regarding the methodology, it is a descriptive research. The method is by case study. Three instruments were used for data collection: participant observation, since the researcher participates in the planning and implementation of RIUFLA; semistructured interviews on the perception of the university actors directly involved with the implementation of RI UFLA and questionnaires through Google Docs sent to those responsible for IRs in ten higher education institutions that are repositories established and PII have made. For data analysis we used content analysis. We conclude that, through the experience of the pilot project, the interviews with the actors and by means of a comparison with the implementation experience of the analyzed institutions, we found what general questions guided by IBICT were adopted by UFLA. However, the IBICT policy presents limitations because it does not include all items necessary for the effective operation of an IR with generic guidelines, shorter deadline than the time needed for implementation and lack of training. As for the view of the interviewees on the policy, it was positive, as they believe it will benefit researchers and bring visibility to the institution. Moreover, it was possible to detect the early barriers and limitations of RIUFLA and seek actions to correct them. Thus, by the implementation experience, it was recommended adjustment actions regarding the restructuring of PIIUFLA, concerning the technical team, the types of documents, more effective outreach strategies and the repeated proposal for a mandatory deposit.